INDEKS MINAT BACA KABUPATEN MAGETAN JAWA TIMUR - Suji Suji; Ni Made Sukartani (Journal of Social and Political Science)
This study examines the index of people's reading interest in Magetan Regency. The Reading Interest Index is one of the supporting components in increasing the population literacy rate. Theoretically and empirically, the level of population literacy is part of the development of human resources (human capital investment) which is found to have the most influence on work productivity and its contribution to development. This study uses a combination of primary data and secondary data to calculate the reading interest index in Mageten Regency. Secondary data were collected from related agencies, such as the Regional Library and Archives Office of Magetan Regency. Primary data were collected from survey activities. The survey was conducted in 3 (three) districts, namely: Magetan, Maospati and Plaosan Districts. These three sub-districts were selected based on regional criteria: East (Maospati); Middle (Magetan); and the West (Plaosan). Two elementary schools, junior high school, SMA-SMK, Diploma Program and 1 (one) University are selected in each district. The results of the calculation of the reading interest index in the 3 (three) selected districts resulted in 74.76 (Arithmetic average) and 74.22 (Geometry average). This value indicates that the reading interest index of the people of Magetan Regency is included in the "sufficient" category (Saepudin, 2015) or the "high" category if it follows the category of the Ministry of Education and Culture (2019). Keywords: Reading Interest Index, Literacy, Human Resources